(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The outcomes of introductionand overwintering in winter 2005-2006are adduced of 35species wood plants in State Enterprise Experimental Farm Novokakhovskoe of Nikita Botanical Garden National Scientific Center.